Impact of the Addition of Baricitinib to Standard of Care Including Tocilizumab and Corticosteroids on Mortality and Safety in Severe COVID-19 - Masiá, Mar; Padilla, Sergio; García, José Alberto; García-Abellán, Javier; Navarro, Andrés; Guillén, Lucía; Telenti, Guillermo; Mascarell, Paula; Botella, Ángela; Gutiérrez, Félix (Frontiers in Medicine, 2021)
Background: Baricitinib is a Janus kinase (JAK) inhibitor with a broader anti-inflammatory activity than tocilizumab and an antiviral potential although no head-to-head trials are available. The benefits of adding baricitinib to patients with COVID-19 experiencing clinical progression despite the standard of care (SOC), including corticosteroids and tocilizumab, are also unknown. Methods: A cohort study included microbiologically confirmed COVID-19 hospitalizations. The primary outcome was 28-day mortality. Secondary outcomes were 60- and 90-day mortality, the composite outcome “28-day invasive mechanical ventilation (IMV) or death” and the safety of the combination. Propensity score (PS) matching was used to identify the association between baricitinib use and the outcomes of interest. Results: Of 1,709 admissions, 994 patients received corticosteroids and tocilizumab and 110 of them received baricitinib after tocilizumab. PS matched 190 (95:95) patients with baricitinib + SOC vs. SOC, of whom 69.5% received remdesivir. No significant effect of baricitinib was observed on 28-day [39 events; adjusted hazard ratio (aHR), 0.76; 95% CI, 0.31–1.86], 60-day (49 events, aHR, 1.17; 95% CI, 0.55–2.52), or 90-day mortality (49 events; aHR, 1.14; 95% CI, 0.53–2.47), or on the composite outcome 28-day IMV/death (aHR, 0.88; 95% CI, 0.45–1.72). Secondary infections during hospitalization were not different between groups (17.9 vs. 10.5%, respectively; p = 0.212) and thromboembolic events were higher with baricitinib (11.6% vs. 3.2%; p = 0.048), but differences vanished after the adjustment [aHR 1.89 (0.31–11.57), p = 0.490]. Conclusion: The addition of baricitinib did not substantially reduce mortality in hospitalized patients with COVID-19 having clinical progression despite the therapy with tocilizumab and corticosteroids. The combination of baricitinib and tocilizumab was not associated with an increased risk of secondary infections or thromboembolic events.